China’s mandarin and tangerine cultivation has not reached the carbon emissions peak - Liu, Jialiang; Zhang, Jingyu; Li, Yingchun; Zong, Shixiang; Ma, Fen; Zhao, Bohan (Mitigation and adaptation strategies for global change, 2024)
China is a world leading mandarin and tangerine producer, and the carbon emissions of mandarin and tangerine directly affect the characteristics and peak time of China’s agricultural carbon emissions. This study applied the life cycle assessment method to calculate the carbon emissions during the planting process of China’s mandarin and tangerine, and evaluated their carbon peak state and analyzed the planting advantages of different provinces based on the carbon economic efficiency (CEE) index. The results indicated that, the averaged carbon emissions per unit area (CA) and per yield (CY) of mandarin in 2020 were 13.9% and 15.8% lower than those in 2006, while CA and CY of tangerine in 2020 were 47.8% and 22.2% lower than those in 2006. Changes of carbon emissions from fertilizer production made great contributions to the decrease in carbon footprint (CF) on the time scale, and differences in CF across regions were mainly caused by fertilizer application. The CA and CY of mandarin were higher than those of tangerine, due to the higher application of nitrogen fertilizer in orchards. Zhejiang and Hubei reached their carbon emissions peaks mainly due to the decrease in agricultural input, while the state of whole China was still in a plateau period. Jiangxi and Zhejiang had significant planting advantages due to their lower CYs and higher CEEs. In conclusion, there are possibilities for low-carbon development of Chinese mandarin and tangerine through targeted mitigation measures such as variety improvement and precise fertilization.